2016
DOI: 10.1093/infdis/jiw396
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of EBV Infection and Antibody Responses in Kenyan Infants With Different Levels of Malaria Exposure Shows Maternal Antibody Decay is a Major Determinant of Early EBV Infection

Abstract: The combination of Epstein-Barr virus (EBV) infection and high malaria exposure are risk factors for endemic Burkitt lymphoma, and evidence suggests that infants in regions of high malaria exposure have earlier EBV infection and increased EBV reactivation. In this study we analyzed the longitudinal antibody response to EBV in Kenyan infants with different levels of malaria exposure. We found that high malaria exposure was associated with a faster decline of maternally derived immunoglobulin G antibody to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…As expected, our data support a strong role of EBV in eBL, and a weak effect of malaria, but suggest that both infections might act jointly on eBL, as shown by the additive interaction between elevated IgGs against EBV and MSP-3. In agreement with this observation, two recent studies have reported that the key determinants of EBV primary infection kinetics in children are the degree of malaria exposure and maternal antibody decay ( 9 , 40 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As expected, our data support a strong role of EBV in eBL, and a weak effect of malaria, but suggest that both infections might act jointly on eBL, as shown by the additive interaction between elevated IgGs against EBV and MSP-3. In agreement with this observation, two recent studies have reported that the key determinants of EBV primary infection kinetics in children are the degree of malaria exposure and maternal antibody decay ( 9 , 40 ).…”
Section: Discussionsupporting
confidence: 70%
“…High IgM levels against VCA-p18 usually indicate recent primary EBV infection, although it may persist for months or might reappear in EBV reactivation. The negative association of high IgM anti-VCA-p18 levels with eBL suggests that newly EBV-infected children might be at lesser risk of eBL compared with children exposed for a longer time, or might indicate that in a malaria endemic region the long-term persistence of anti-VCA IgM responses may be associated with a better control of EBV infection ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was not surprising to find no correlation with EBV antibody titers using a single time point, because our past studies have demonstrated longitudinal variability in EBV antibody titers. 3,44 However, malaria antibody profiles have been used as an indicator of cumulative and recent past exposure in the absence of an active infection. 45 KIR licensing in malaria-exposed and eBL children favors inhibitory signals Figure 2F), we observed significantly higher expression for Kisumu and eBL children compared with Nandi children (P 5 .04 and .01, respectively).…”
Section: Cd56mentioning
confidence: 99%
“…Our series of Fc-binding, hemagglutination inhibition (HI), and focus reduction assays (FRA) across the severe influenza infection cohorts allowed us to analyze the kinetics of the responses. To account for the limited series of samples and variable times after infection when the samples were taken from each subject, we modeled the peak of ADCC or NAb responses across data collected from all subjects at all time points tested (2-5 longitudinal samples per subject) based on standard rise and decay characteristics of Abs as previously described (34). The primary data used for modeling is shown in Supplemental Figures 6 and 7.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…To analyze differences between influenza-specific Ab kinetics, we used a log linear regression as previously described (34). Ab responses increased exponentially until a certain time (T peak ), after which they decrease exponentially.…”
Section: Modeling the Kinetics Of Influenza-specific Ab Responsesmentioning
confidence: 99%